PENGEMBANGAN MODUL MATERI STATISTIKA MELALUI PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS XII SMA - Yohana S. N. Ndruru (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
The purpose of this research is to produce a valid, practical, and effective statistics module that can improve students' understanding of concepts. ThisiresearchiisiDevelopmentiResearch, ithe developmentimodeliusediisitheiADDIEimodel, namly Analisis, Design, Development, Implementation, and Evaluation. The data colection instruments use were questionnaires and tests. While the data analysis techniques are qualitative data analysis and quantitativ data analysis. The research results for the level of validity of the module seen from the material aspects, media aspects, and language aspects obtained with a proportion of 84.04% and are in the Valid criteria. The practicality test results from the limited trial student response numbers obtained an average score of 4.75 in the very practical category, and for field trial students an average score of 4.47 was obtained in the very practical category. The results of the effectiveness test of student learning outcomes for limited trials obtained the proportion of 80.67% in the effective category, and for students in the field trials obtained the proportion of 80.24% with the effective category. To increase understanding of concepts in limited trials and field trials, students each obtained an average score of 0.54 and 0.65 in the moderate category. So it can be concluded that the module is valid, practical and effective and can improve students' understanding of concepts.